Effect of video assistant referee (VAR) system on match statistics: a nine-year retrospective analysis of the Brazilian national league - Bedo, B; Assis, R; Alves, A; Palucci Vieira, L; Aquino, R; Moura, F. (International Journal of Sports Science & Coaching, 2025)
This study aimed to assess the impact of the Video Assistant Referee (VAR) system on soccer match statistics during the Brazilian Serie A/first division, using nine years of retrospective data from 3420 matches. Between 2015 and 2018, 1520 matches were played without VAR, while from 2019 to 2023, 1900 matches included using the VAR system. The variables include fouls, goals, offsides, penalties, playing time in each half, total playing time, and red and yellow cards. The data were obtained through an API and cross-verified with match summaries. A generalized linear model and pairwise z-tests were applied to compare seasons before and after the implementation of VAR, with a 95% significance level. The results revealed that VAR reduced the number of offsides and increased playing time in both halves, resulting in longer overall match durations. No significant changes were observed in yellow cards, red cards, penalties, or goals. These findings are consistent with results reported in other major leagues, suggesting that cultural factors may play a role in how VAR influences match statistics across different contexts.